2009
DOI: 10.1002/em.20492
|View full text |Cite
|
Sign up to set email alerts
|

The role of paraoxonase polymorphisms in the induction of micronucleus in paraoxon‐treated human lymphocytes

Abstract: Human paraoxonase-1 (PON1) is a high-density lipoprotein-associated enzyme that has a role in the detoxification of organophosphorus compounds by hydrolyzing the bioactive oxons. PON1 polymorphims are responsible, at least in part, for the variation in the catalytic activity and expression of the enzyme and have been associated with susceptibility to organophosphorus pesticide toxicity, mainly neurotoxicity. The aim of this study was to determine whether paraoxon induced micronuclei and to examine the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Methyl parathion was also found genotoxic to human peripheral blood lymphocytes under in vitro conditions [ 22 ]. Rojas-García et al [ 23 ] reported the dose dependent increase in micronucleus in peripheral human blood lymphocytes with paraoxon (an active metabolite of parathion). They treated the peripheral human blood lymphocytes with range of 1–25 μ M concentrations of paraoxon and found dose dependent DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl parathion was also found genotoxic to human peripheral blood lymphocytes under in vitro conditions [ 22 ]. Rojas-García et al [ 23 ] reported the dose dependent increase in micronucleus in peripheral human blood lymphocytes with paraoxon (an active metabolite of parathion). They treated the peripheral human blood lymphocytes with range of 1–25 μ M concentrations of paraoxon and found dose dependent DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive review on the genotoxic effect of commonly used pesticides by persons in the work place and those employed in the chemical industry was conducted by Bolognesi et al (5), highlighting the importance of genotoxic biomonitoring in human populations who might be at a greater risk of cancer. Interestingly, many of the studies on increased micronucleus frequency in pesticideexposed populations have established the incidence of specific polymorphisms within Paraoxonase 1 (PON1), an enzyme that detoxifies organophosphates (5,119). This is an example of a gene-environment interaction that could help explain the modification of the relation between occupational exposures and aneuploidic events by genotype.…”
Section: Environmental Toxins and Chromatin Instabilitymentioning
confidence: 99%
“…These limitations include some aspects related to enzyme kinetics and pharmacokinetics, which can be modified by internal and external factors, and physio-pathological conditions that are yet unknown for temephos. For example, López-Flores et al (2009) reported that chronic exposure to OPs causes a depletion of the PON activity; this exacerbates cholinergic effects associated with oxon formation. , In the same sense, the polymorphism of PON modulates the magnitude of DNA damage caused by OP exposure and the possible inhibition of some CYP isoforms by temephos, as has been described for other OPTs, such chlorpyrifos, forate, and fonofos. All these factors could modify the rate of each reaction and change the final proportion of metabolites formed. The biotransformation pathway proposed in this work is like a map in that if something blocks a route, another possible route, or reaction, will be utilized.…”
Section: Discussionmentioning
confidence: 97%